Role of magnetic resonance imaging and its new techniques in detection of tumour viability and complications after thermal ablation therapy for hepatocellular carcinoma - Bahaa Eldin Mahmoud Hussein Mahmoud; Ahmed Hosni Kamel; Hamed Samir Elghawaby; Mohamed Mahmoud Nabeel (cairo : Bahaa Eldin Mahmoud Hussein Mahmoud, 2014)
MRI with its new functional imaging techniques including dynamic study and diffusion imaging is a powerful tool in detection of tumour viability and complications after thermal ablation of hepatocellular carcinoma. We found that dynamic study is the gold standard in detection of recurrent lesions. Well defined nodular enhancement, thick irregular marginal enhancement or gross enlargement of the lesion with arterial phase enhancement and contrast wash out were considered positive for malignancy. We also found that ADC measurement is reliable in differentiation between the recurrent malignant lesions and the post treatment reactive and vascular tissue changes with significant statistical differences between them
Thesis (Ph.D.) - Cairo University - Faculty of medicine - Department of Radio-diagnosis
Issued also as CD
Keywords: Hepatocellular carcinoma; MRI; Thermal ablation